Some Problems with Robert Alexy's Account of Legal Validity: The Relevance of the Participant's Perspective - Gaido, Paula Marina (2012)
This article examines Robert Alexy's account of legal validity. It concludes that Alexy's account of legal validity lacks sufficient support given the author's methodological commitments. To reach that conclusion, it assesses the plausibility of simultaneously maintaining that the participant's perspective has conceptual privilege in the explanation of the nature of law, that legal discourse is a special case of general practical discourse, and that unjust considerations can be legally valid norms.